European Project Semester - Budzinska, Grazyna (2022)
This chapter aims to introduce the European Project Semester concept and the network of providers together with historical and current data on participants and providers. EPS is a one-semester international exchange program designed for engineering, product designers, and business undergraduates. It embraces student-centered project-based learning and multicultural and transdisciplinary teamwork to help students develop the competencies and skills required for the 21st century. It was created in 1995 in Denmark to prepare future engineers for global challenges, and it combines scientific and technical education, ethical and sustainability-driven problem-solving, intercultural communication, and teamwork. EPS has since been adopted by 19 European higher education institutions, establishing a network of EPS providers across Europe. The network offers international students a wide range of European study locations and cultural insights and, above all, the opportunity to enjoy the EPS learning experience. The number of alumni shows the program's attractiveness, range, and vitality.